1998
DOI: 10.1074/jbc.273.50.33517
|View full text |Cite
|
Sign up to set email alerts
|

Solution Conformation of the Synthetic Bovine Proenkephalin-A209–237 by 1H NMR Spectroscopy

Abstract: Proenkephalin-A has been described to generate enkephalins, opoid peptides, and several derived peptides, which display various biological effects, including antinociception and immunological enhancement. Recently, we have isolated from bovine chromaffin granules a new antibacterial peptide, named enkelytin, which corresponds to the bisphosphorylated form of PEAP 209 -237 (Goumon, Y., Strub, J. M., Moniatte, M., Nullans, G., Poteur, L., Hubert, P., Van Dorsselaer, A., Aunis, D., and Metz-Boutigue, M. H. (1996)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…In conclusion, the antibacterial activity of enkelytin toward M. luteus is directly related to three structural parameters: (i) the length of the peptidic chain, (ii) the natural conformational constraints induced by the three proline residues Pro 212 , Pro 214 , Pro 227 , and (iii) the phosphorylation of Ser 221 and Ser 223 . Computer Model of PEAP 209 -237 -An extensive study using biophysical techniques has been carried out on PEAP 209 -237 in our laboratory (89). We refer to some of these data to draw up the computer model of PEAP 209 -237 fitting with the biological activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In conclusion, the antibacterial activity of enkelytin toward M. luteus is directly related to three structural parameters: (i) the length of the peptidic chain, (ii) the natural conformational constraints induced by the three proline residues Pro 212 , Pro 214 , Pro 227 , and (iii) the phosphorylation of Ser 221 and Ser 223 . Computer Model of PEAP 209 -237 -An extensive study using biophysical techniques has been carried out on PEAP 209 -237 in our laboratory (89). We refer to some of these data to draw up the computer model of PEAP 209 -237 fitting with the biological activity.…”
Section: Resultsmentioning
confidence: 99%
“…Several natural and synthetic enkelytin-derived peptides were also tested to determine the structural features necessary for the antibacterial activity. Then, the activity of these peptides was related with the ␣-helical structure, obtained from recent 1 H NMR data (89).…”
Section: Resultsmentioning
confidence: 99%
“…The antibacterial mechanism of the chromaffin peptides has not been elucidated; however, recent 1 H nuclear magnetic resonance spectroscopic analysis of synthetic nonphosphorylated enkelytin demonstrated that the peptide adopts a proline-kinked amphipathic helical structure in 50% (vol/vol) trifluoroethanol (10). The structure of the phosphorylated form of enkelytin has not been determined; however, phosphorylation is likely to change the peptide's conformation through electrostatic repulsion or by divalent metal ion binding (5,10). The binding of divalent cations may act to stabilize the peptide structure but also may help to localize the peptide at the bacterial cell surface.…”
Section: Discussionmentioning
confidence: 99%
“…A number of secondary structures of antimicrobial peptides, broadly representative of the above structural groups, have been determined by two-dimensional nmr, either in solution or in model membrane environments. They include cecropins, 89 -92 magainins, [93][94][95] PGLa, 96 sarcotoxin, 97 buforin, 98 caerin, 99 bactenecins, 100 enkelytin, 101 histatin, 102 ranalexin, 103 thanatin, 104 protegrin, 105 tachyplesin, 106 different types of defensins, [107][108][109][110][111][112][113][114][115] and drosomycin.…”
Section: Structural Aspectsmentioning
confidence: 99%